Simple and efficient protocol to isolate and culture brain microvascular endothelial cells from newborn mice - Nicolicht-Amorim, Priscila; Delgado-Garcia, Lina M.; Nakamura, Thabatta Karollynne Estevam; Courbassier, Natália Rodrigues; Mosini, Amanda Cristina; Porcionatto, Marimelia A. (Frontiers in Cellular Neuroscience, 2022)
The neurovascular unit (NVU) is a multicellular structure comprising of neurons, glial cells, and non-neural cells, and it is supported by a specialized extracellular matrix, the basal lamina. Astrocytes, brain microvascular endothelial cells (BMECs), pericytes, and smooth muscle cells constitute the blood–brain barrier (BBB). BMECs have a mesodermal origin and invade the nervous system early in neural tube development, forming the BBB anatomical core. BMECs are connected by adherent junction complexes composed of integral membrane and cytoplasmic proteins. In vivo and in vitro studies have shown that, given the proximity and relationship with neural cells, BMECs acquire a unique gene expression profile, proteome, and specific mechanical and physical properties compared to endothelial cells from the general vasculature. BMECs are fundamental in maintaining brain homeostasis by regulating transcellular and paracellular transport of fluids, molecules, and cells. Therefore, it is essential to gain in-depth knowledge of the dynamic cellular structure of the cells in the NVU and their interactions with health and disease. Here we describe a significantly improved and simplified protocol using C57BL/6 newborn mice at postnatal day 1 (PND1) to isolate, purify, and culture BMECs monolayers in two different substrates (glass coverslips and transwell culture inserts). In vitro characterization and validation of the BMEC primary culture monolayers seeded on glass or insert included light microscopy, immunolabeling, and gene expression profile. Transendothelial electrical resistance (TEER) measurement and diffusion test were used as functional assays for adherent junction complexes and integrity and permeability of BMECs monolayers. The protocol presented here for the isolation and culture of BMECs is more straightforward than previously published protocols and yields a high number of purified cells. Finally, we tested BMECs function using the oxygen–glucose deprivation (OGD) model of hypoxia. This protocol may be suitable as a bioscaffold for secondary cell seeding allowing the study and better understanding of the NVU.